Ecofriendly regioselective one-pot synthesis of chromeno[4,3-d][1,2,4]triazolo[4,3-a]pyrimidine derivatives - Gomha, Sobhi Mohamed; Badrey, Mohamed Gomaa (European Journal of Chemistry, 2013)
The reaction between 2-mercapto-3H-chromeno[4,3-d]pyrimidine-4,5-dione (1) or its 2-methylthio derivative (7) with hydrazonoyl halides (2) in dioxane under ultrasound irradiation in the presence of chitosan yielded chromeno[4,3-d][1,2,4]triazolo[4,3-a]pyrimidine derivatives (5a-r). On the other hand, the reaction of compound 1 with the appropriate active chloromethylene compounds (9b, h and m) followed by coupling the products with benzenediazonium chloride afforded the azo coupling products which converted in situ to compound 5. The reaction mechanism was proposed and the structure of the newly synthesized compounds were established on the basis of spectral data (Mass, IR, 1H and 13C NMR) and elemental analyses.